2007
DOI: 10.1002/jbm.b.30810
|View full text |Cite
|
Sign up to set email alerts
|

Host response to sponge implants differs between subcutaneous and intraperitoneal sites in mice

Abstract: Synthetic matrices have been used widely to repair and/or to replace biological tissues. However, there is relatively little information on the effect of different anatomical compartments on the host response to foreign implants. We have analyzed such responses to sponge implants in subcutaneous and in intraperitoneal sites in mice at days 3, 5, and 8 postimplantation by measuring inflammation, angiogenesis, and production of proangiogenic/inflammatory cytokines. The angiogenic response, assessed by hemoglobin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
42
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 22 publications
5
42
0
3
Order By: Relevance
“…It is intriguing that the reported anti-inflammatory effects of propolis are in contrast with the results presented here, particularly those from our group, which showed propolis to exert an anti-inflammatory effect on implants located subcutaneously in mice [16]. We have previously demonstrated that the anatomical site markedly influences the host response to a synthetic matrix [19] and, herein, we extend this observation to the host response to a pharmacological compound. It is striking that by up-regulating pro-inflammatory pathways, propolis has down-regulated angiogenesis and fibrosis in the peritoneal implant.…”
Section: Discussionsupporting
confidence: 43%
“…It is intriguing that the reported anti-inflammatory effects of propolis are in contrast with the results presented here, particularly those from our group, which showed propolis to exert an anti-inflammatory effect on implants located subcutaneously in mice [16]. We have previously demonstrated that the anatomical site markedly influences the host response to a synthetic matrix [19] and, herein, we extend this observation to the host response to a pharmacological compound. It is striking that by up-regulating pro-inflammatory pathways, propolis has down-regulated angiogenesis and fibrosis in the peritoneal implant.…”
Section: Discussionsupporting
confidence: 43%
“…The intraperitoneal implants were shown to be extensively adhered to other organs (liver, intestines), highly vascularized, infiltrated with inflammatory cells, fibroblast-and mesothelial-like cells, and to produce pro-inflammatory and proangiogenic cytokines (Mendes et al 2007). In this study, we used this murine model of peritoneal adhesion to investigate the effects of controlling adhesion development through inhibition of its key components (angiogenesis, inflammation and fibrosis) with the PDE inhibitors cilostazol and PTX.…”
Section: Discussionmentioning
confidence: 98%
“…We recently reported that implantation of synthetic matrix in the peritoneal cavity of mice elicited the formation of adhesions whose components angiogenesis, inflammation, and fibrosis (common features of human adhesions and of experimental animal models) were identified. In this model, we were able to assess many parameters of the newly induced fibrovascular tissue, including the formation of new blood vessels, the levels of inflammatory and angiogenic cytokines, and the infiltration of leukocytes (Mendes et al 2007).…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%
“…The extent of mononuclear cells in the sponge implants was quantitated by measuring the levels of the lysosomal enzyme, N-acetyl-glucosaminidase (NAG), present in high levels in activated macrophages [12], [15][16]. The implants were homogenized in 2 mL NaCl solution (0.9% w/v) containing 0.1% v/v Triton X-100 (Promega, Madison, WI) and centrifuged at 3000 rpm; 10 min at 4°C.…”
Section: Methodsmentioning
confidence: 99%